A novel application of the culotte stent technique to bail out a jailed common iliac artery - Hideto Sangen, MD; Shuhei Tara, MD, PhD; Takahisa Tanaka, MD; Hitoshi Takano, MD, PhD; Kunio Tanaka, MD, PhD; Wataru Shimizu, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2017)
Implanting a self-expandable stent at the ostium of the common iliac artery (CIA) may lead to coverage of the orifice of the contralateral CIA. Here, we describe a novel application of the culotte stent technique using a balloon-expandable stent to bail out an ostial stenotic legion of a jailed CIA due to prior self-expandable stent placement. The bilateral CIAs were revascularized by culotte stenting, and patency of the stents was confirmed 3 years after the procedure. The culotte stent technique was successfully applied to an ostial stenotic lesion of a jailed CIA.